(untitled) (European Journal of Pure and Applied Mathematics, 2018)
In this paper, we investigate some combinatorial sequences based on Daehee andÂ Changhee numbers and polynomials, then derive their moment representations in use of probabilistic method. We also provide identities related to Daehee numbers, derangement numbers,Â Cauchy numbers of the second kind, and Stirling numbers of the first kind.